2018
DOI: 10.1109/twc.2017.2777966
|View full text |Cite
|
Sign up to set email alerts
|

Gallager Bound for MIMO Channels: Large- $N$ Asymptotics

Abstract: Abstract-The use of multiple antenna arrays in transmission and reception has become an integral part of modern wireless communications. To quantify the performance of such systems, the evaluation of bounds on the error probability of realistic finite length codewords is important. In this paper, we analyze the standard Gallager error bound for both constraints of maximum average power and maximum instantaneous power. Applying techniques from random matrix theory, we obtain analytic expressions of the error ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Based on the above results, we will investigate the asymptotic distribution of the MID defined in (16) with the exact energy constraint S = .…”
Section: Theorem 1 (First-order Results Regarding the MI Of Rayleighp...mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the above results, we will investigate the asymptotic distribution of the MID defined in (16) with the exact energy constraint S = .…”
Section: Theorem 1 (First-order Results Regarding the MI Of Rayleighp...mentioning
confidence: 99%
“…FBL Analysis Single-Rayleigh Channel [28] [15], [16] Rayleigh-product Channel [21], [23]- [27] This work the full-rank independent Rayleigh MIMO channels, which, as evident in [18], is incapable of characterizing the reducedrank behavior of MIMO systems due to the lack of scatterers around the transceivers. Although the rank of the channel was considered in [10], the i.i.d.…”
Section: Shannon Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the estimation is consistent, not only when the sample size increases without bound for a fixed observation dimension, but also when the observation dimension increases to infinity at the same rate as the sample size increases [33][34][35]. This finding has found many applications in signal processing for communication, radar, sonar and so on [36][37][38][39][40][41][42][43][44][45][46]. Recently, [43] applies the theory to directly estimate the inverse covariance matrix for spatial beamforming and shows superior performance under high dimension and finite training samples.…”
Section: Introductionmentioning
confidence: 89%
“…As in the development of RMT-FD-STAP, the RMT-RD-STAP corrects the clutter-related eigenvalues by (44) and thus performs better than the RD-STAP for any local clutter DOFs Q rd .…”
Section: B Reduced-dimension Stap Using Rmtmentioning
confidence: 99%